ANALISIS PERILAKU KONSUMTIF MAHASISWA DALAM PERSPEKTIF EKONOMI ISLAM : Studi Kasus Mahasiswa Kota Jambi - Tuty Alawiyah; Agustina Mutia; Ferry Saputra Tanjung (Pusat Riset dan Inovasi Nasional, 2023)
Consumption is inseparable from the rules and requirements set by Islamic teachings. However, in consuming, we must behave according to the standards and ethics of consumption in the Islamic economy. Therefore, in the order of life, Islam has regulated how humans can carry out activities that can be consumed so that they are beneficial to their lives. To achieve this goal, an understanding of Muslim consumer behavior is needed. In this case, Yusuf Al-Qardhawi explains how to consume, rules and correct behavior according to the recommendations of the Qur'an and Sunnah and how to apply them in life in an Islamic economic perspective. In consuming, Jambi City students must follow Yusuf Al-Qardhawi's consumer standards and ethics. The type of research used is descriptive qualitative. The data in this study were obtained from primary data and secondary data. With data collection techniques, namely interviews, observation and documentation. The results of this study indicate several things that happen to students who drink liquor in the city of Jambi, namely: 1) Spending wealth for good and staying away from miserliness can be interpreted as using assets owned for self-interest as well as a way to worship Allah SWT. Jambi City students have not fully implemented the concept of spending wealth properly and avoiding extravagance or israf. 2) Islam prohibits excessive consumption of wealth for useful and not excessive purposes (waste/israf). 3) Modesty in spending wealth can be seen from the attitude between miserly and miserly, excessive behavior and attitudes in between, including the attitude of luxury. This implementation should be in everyone.